Magnetic and non-magnetic. - Royston, Angela, 1945- (Chicago, IL : Heinemann Library, 2003)
Provides a simple explanation of the differences between magnetic and non-magnetic materials.
What does a magnet do? -- Magnetic materials -- Are all metals magnetic? -- Non-magnetic materials -- Can magnetism pass through water? -- Can magnetism pass through other materials? -- Using magnets -- Magnet in toys -- Magnets and fridges -- Magnetic rocks -- The earth is a magnet -- Using the earth's magnet -- Compasses.
Includes bibliographical references ( p. 31) and index.
Keywords: Magnetism; Magnets